Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters